2003
DOI: 10.1007/bf02915250
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of spironolactone in patients with severe heart failure

Abstract: This economic evaluation suggests that the addition of spironolactone to standard therapy for patients with severe chronic heart failure is not only safe and effective, but is highly cost-effective in the Irish healthcare setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…29, [118][119][120][121][122] None of these studies attempted to undertake a direct comparison of the cost-effectiveness of spironolactone versus eplerenone. Two of the studies reported the cost-effectiveness of spironolactone versus standard care in patients with severe chronic HF and the remainder evaluated the cost-effectiveness of eplerenone versus standard care in patients with HF after acute MI (AMI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29, [118][119][120][121][122] None of these studies attempted to undertake a direct comparison of the cost-effectiveness of spironolactone versus eplerenone. Two of the studies reported the cost-effectiveness of spironolactone versus standard care in patients with severe chronic HF and the remainder evaluated the cost-effectiveness of eplerenone versus standard care in patients with HF after acute MI (AMI).…”
Section: Resultsmentioning
confidence: 99%
“…A useful summary of the wider set of cost-effectiveness studies for eplererone has been previously published. 33 The following sections provide a detailed critique of the cost-effectiveness evidence from the three main studies included 29,118,120 and an assessment of the quality and relevance of the data from the perspective of the UK NHS. A quality assessment checklist for each study is provided in Appendix 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in these studies there was a drop of only 5%. This is probably caused by the studies conducted using specific diuretic that spironolactone 16 . At the cost of services and laboratory results, it was found that the group of diuretics and ACE inhibitors to pay more than the diuretic group without ACE inhibitors, but was not statistically Tabel 6.…”
Section: Discussionmentioning
confidence: 99%
“…The number of inpatient days was taken from Daly et al (2007: 69 (2006: 11) The unit costs were based on a study by Tilson et al (2003) GP Consultations (public health system)…”
Section: Public Psychiatric Hospitalsmentioning
confidence: 99%